Structural Basis for Specific Recognition of Substrates by Sapovirus Protease - Yokoyama, Masaru; Oka, Tomoichiro; Kojima, Hirotatsu; Nagano, Tetsuo; Okabe, Takayoshi; Katayama, Kazuhiko; Wakita, Takaji; Kanda, Tadahito; Sato, Hironori (Frontiers in Microbiology, 2012)
Sapovirus (SaV) protease catalyzes cleavage of the peptide bonds at six sites of a viral polyprotein for the viral replication and maturation. However, the mechanisms by which the protease recognizes the distinct sequences of the six cleavage sites remain poorly understood. Here we examined this issue by computational and experimental approaches. A structural modeling and docking study disclosed two small clefts on the SaV protease cavity that allow the stable and functional binding of substrates to the catalytic cavity via aromatic stacking and electrostatic interactions. An information entropy study and a site-directed mutagenesis study consistently suggested variability of the two clefts under functional constraints. Using this information, we identified three chemical compounds that had structural and spatial features resembling those of the substrate amino acid residues bound to the two clefts and that exhibited an inhibitory effect on SaV protease in vitro. These results suggest that the two clefts provide structural base points to realize the functional binding of various substrates.